Hemichordates’ diffuse “skin brain” shows unexpected complexity - Kerbl, Alexandra; Jékely, Gáspár (PLoS biology, 2023)
Hemichordates are close relatives of chordates. Their nervous system patterning is chordate-like, but their neural architecture remains unexplored. A new study in PLOS Biology reveals an unexpected neuroanatomical complexity in these animals, also informing chordate origins.